Perkembangan Penyakit Moler (Fusarium Oxysporum F.Sp Cepae) pada Sentra Produksi Bawang Merah di Kabupaten Probolinggo - Suhartiningsih Dwi Nurcahyanti; Muhammad Iqbal Sholeh (Jember University Press, 2023)
East Java also has a shallot production center, namely in the Probolinggo area. Generally, residents of the Probolinggo area make a living as farmers. The land cultivated as agricultural land is generally one's own. The area of land owned by farmers is in the range of 0.25 meters to above 1 hectare. The land is generally used to cultivate horticultural crops, especially shallots. This farmer in Probolinggo chose the cultivation of shallot crops because it has high economic value and growing potential. Onion plants are vegetable crops in the form of bulbs with high economic value, because almost every household consumer needs them. This shallot can be used as a seasoning in cooking or as medicine. As a result, the need for shallots has increased so that many farmers cultivate onion crops intensively. Currently, the cultivation of onion plants is experiencing disturbances due to the attack of moler disease caused by the fungus Fusarium oxysporum f.sp. cepae (FoCe). FoCe fungus is a fungus that causes moler disease in onion crops. The disease can affect both the roots and bulbs of onions. Symptoms caused by onion plants are rotting of the roots so that they are easily removed, leaves drooping, twisting, shriveling, and rotting, as well as rotting of the bulbs and there is a white fungus that can cause the onion plant to die. This fungus can be transmitted from one plant to another through the soil.This study was conducted to determine the development of F.oxysporum disease in the onion production center in Probolinggo Regency. This research was conducted in several sub-districts, namely in Pajarakan District, Gending District, and Dringu District. Data collection on the development of moler disease using qualitative data from interviews with onion growers. The data used is in the form of observations of the impact of moler disease which is common to attack onion plants. The variables asked during the interview were the symptoms of moler disease that occurs when attacking onion plants, the factors causing the spread of moler disease in shallots, and the impact of moler disease attacks on onion plants. The data obtained were then analyzed using descriptive to describe the development and characteristics of the pathogen Fusarium oxysporum. The results showed that the development of moler disease in shallot production centers in Probolinggo Regency, especially in Pajarakan District, Gending District, and Dringu District, has a high incidence and severity of the disease. This is caused by internal factors such as the selection of varieties that are less resistant and the presence of external factors such as the tendency of farmers not to spray fungicides on planting. The characteristics of the fungus F. oxysporum observed in PDA media by taking onion samples in three districts, namely pajakan, gending and drigu, have a white color at the beginning of development and subsequently yellow or cream, shaped like cotton and circular.